Business transformation through web services - Currie, Wendy, 1960-; Weerakkody, Vishanth; Wang, Xinkun (Journal of enterprise information management, 2004)
Despite the vendor "hype" surrounding e-business, the dot.com collapse and economic decline in the technology sector has led many firms to question the value-creating aspects of e-business models. This special issue on Business transformation through Web services explores the business-specific and technical dimension of this emerging model. Previously published in: Journal of Enterprise Information Management, Volume 17, Number 5, 2004.